Dual gold catalysis: synthesis of fluorene derivatives from diynes - Bucher, Janina; Wurm, Thomas; Taschinski, Svenja; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2017)
1,5-Diyne systems bearing one terminal and one benzyl- or allyl-substituted alkyne attached to an aromatic backbone were converted in the presence of a gold catalyst. In a dual gold-catalyzed process, gold vinylidenes are formed that selectively undergo formal CH insertion into the C(sp2)-H bond of the offered unsaturated systems. If H atoms are present in the propargylic position, a subsequent isomerization to the aromatic system takes place leading to 9H-fluorene and 11H-benzo[b]fluorene derivatives as final products. In the case of a quaternary carbon in the propargylic position no further aromatization is observed and 10H-benzo[b]fluorene derivatives are obtained in high yield.
Online published: 8 December 2016